Bibliometric analysis of global research trends in magnetic resonance imaging studies of substantia nigra in Parkinson’s disease (2001–2024) - Jiang, Mei; Deng, Xu; Qiu, Zixiong; Li, Jie; Song, Zifan; Chen, Xiaoshuai; Chen, Ruiqi; Huang, Xianzhi; Cui, Xiaojun; Fu, Yuan (Frontiers in Aging Neuroscience, 2024)
Background: Parkinson's disease (PD) is a globally prevalent neurodegenerative disorder, primarily characterized by muscle rigidity, resting tremor, and bradykinesia. The incidence of PD is rapidly escalating worldwide. Numerous studies have been conducted on the application of magnetic resonance imaging (MRI) in investigating the substantia nigra (SN) in PD patients. However, to date, no bibliometric analysis has been performed on this specific research area. Therefore, this study aimed to provide a comprehensive analysis of the current status in MRI research on the SN in PD patients.: MRI study records related to the SN in PD patients from 2001 to 2024 were searched by using the Web of Science Core Collection (WOSCC) database and then the CiteSpace and VOSviewer were used to conduct bibliometric analysis. Results: Our analysis found that the number of published articles related studies on MRI of the SN in PD showed an overall upward trend over the past decade, in which Lehericy, Stephane, Du, Guangwei, and Huang, Xuemei are the top three authors with the most articles. Additionally, USA, China and Germany are the main contributors to MRI studies of SN in PD.